miR-429-3p mediates memory decline by targeting MKP-1 to reduce surface GluA1-containing AMPA receptors in a mouse model of Alzheimer's disease - Man Luo; Yayan Pang; Junjie Li; Lilin Yi; Bin Wu; Qiuyun Tian; Yan He; Maoju Wang; Lei Xia; Guiqiong He; Weihong Song; Yehong Du; et al. (Elsevier, 2024)
Alzheimer's disease (AD) is a leading cause of dementia in the elderly. Mitogen-activated protein kinase phosphatase 1 (MKP-1) plays a neuroprotective role in AD. However, the molecular mechanisms underlying the effects of MKP-1 on AD have not been extensively studied. MicroRNAs (miRNAs) regulate gene expression at the post-transcriptional level, thereby repressing mRNA translation. Here, we reported that the microRNA-429-3p (miR-429-3p) was significantly increased in the brain of APP23/PS45 AD model mice and N2AAPP AD model cells. We further found that miR-429-3p could downregulate MKP-1 expression by directly binding to its 3'-untranslated region (3' UTR). Inhibition of miR-429-3p by its antagomir (A-miR-429) restored the expression of MKP-1 to a control level and consequently reduced the amyloidogenic processing of APP and Aβ accumulation. More importantly, intranasal administration of A-miR-429 successfully ameliorated the deficits of hippocampal CA1 long-term potentiation and spatial learning and memory in AD model mice by suppressing extracellular signal-regulated kinase (ERK1/2)-mediated GluA1 hyperphosphorylation at Ser831 site, thereby increasing the surface expression of GluA1-containing α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs). Together, these results demonstrate that inhibiting miR-429-3p to upregulate MKP-1 effectively improves cognitive and synaptic functions in AD model mice, suggesting that miR-429/MKP-1 pathway may be a novel therapeutic target for AD treatment.